PERSEPSI SISWA TERHADAP PELAYANAN PRIMA DI SMA NEGERI 2 PAINAN - Afni Rahmadanti (Universitas Negeri Padang, 2015)
The goal of this research are to see information about the exellent service the library. population is 896 students and the sample is 90 students that taken by proporsional random sampling research. The instrument of this research is question with Likert scale models that had tested for validity and reliability. Data analyzed using mean score. The result of this research is that there is studentsatHigh School in the country 2 Painan.Key word : exellent service